Lack of evidence for an association between seminoma and human papillomavirus infection using GP5+/GP6+ consensus primers. Issue 1 (16th October 2012) - Bertazzoni, Giorgia; Sgambato, Alessandro; Migaldi, Mario; Grottola, Antonella; Sabbatini, Anna Maria Teresa; Nanni, Nadia; Farinetti, Alberto; Iachetta, Francesco; Giacobazzi, Elisabetta; Pecorari, Monica; Bonetti, Luca Reggiani
Abstract Testicular germ cell tumors account for about 1% of all cancers. The incidence of these tumors is increasing and they represent the most common solid malignancies of young men aged 15–40 years with seminoma being one of the most common histotype. Pathogenesis of testicular germ cell tumors remains unknown and, although cryptorchidism is considered the main risk factor, there is evidence of an association with environmental and genetic risk factors. Human papillomaviruses (HPV) are a family of DNA viruses and represent a major risk factor for cervical cancer. In addition, they have been associated with other human non‐malignant and malignant diseases, including breast and head and neck cancer. HPV sequences have been detected throughout the male lower genitourinary tract as well as in seminal fluid and an increased testicular tumorigenesis has been reported in HPV transgenic mice. Aim of this study was to evaluate the potential involvement of HPV in human testicular tumorigenesis. Real‐time PCR employing GP5+/GP6+ consensus HPV primers was used to examine the presence of HPV sequences in a subset of human seminoma (n = 61) and normal testicles (n = 23). None of the specimens tested displayed the presence of HPV DNA. These findings do not support an association between HPV and human seminoma and warrant further studies to assess definitively the role of these viruses in human testicular tumorigenesis. J. Med. Virol. 85:105–109, 2012. © 2012 Wiley Periodicals, Inc.